Moralidade anti-heroica contemporânea : estudo comparativo entre os personagens Tony Soprano e Walter White - Pereira, Guilherme Mendes (2019)
TV series such as The Sopranos and Breaking Bad with their antihero protagonists (Tony Soprano and Walter White) have brought narrative, aesthetic and thematic innovations, broadening the cinematographic horizon beyond standards that, until recently, were more or less homogeneous. In this study, it is argued that such narratives and their antiheroes conform allegories to the fortune of contemporary morality — drawn by analysts such as Lipovetsky (1994) and Bauman (1997). This material contrasts with the singular typology of the American anti-hero of the literary fictional romances of the 1960s, developed by Simmons (2008). If this anti-hero emerged in a countercultural context and had an important role of social and political criticism, his postmodern double is antagonistic, extolling, in turn, aspects dictated by the mainstream in contemporary times, such as individualism, consumerism and the weakening of moral responsibility. From a theoretical survey and the comparative analysis of the communicational products and the antiheroes inserted here, it is observed that these, as well as the conflicts, polemics, representations and provocations that evoke, have potency, by allowing the audience to dialogue and philosophical exercise on the issues they develop.